Availability and trend of dissemination of cardiac rehabilitation in China: report from the multicenter national registration platform between 2012 and 2021 - Zhang, Sisi; Ding, Rongjing; Chen, Sikun; Meng, Xiaoping; Jianchao, Li; Wang, Dao Wen; Hu, Dayi (Frontiers in Cardiovascular Medicine, 2023)
The study aimed to evaluate the current status of cardiac rehabilitation programs in China by registering and tracking patients undergoing CR programs in the database. Data were extracted from the online registry platform of the China Society of Cardiopulmonary Prevention and Rehabilitation from February 2012 to December 2021. Overall, data on 19,896 patients with cardiovascular diseases (CVDs) from 159 hospitals in 34 provinces of China were extracted. From a time point of view, the number of patients who had undergone CR and institutions that perform CR showed the first decline in 2009 and then increased until 2021. From a geographic point of view, the degree of participation varied greatly among regions, most of which were concentrated in eastern parts of China. A higher population of patients who underwent CR were male, aged less than 60 years, with low-a risk for coronary heart disease (CHD), and tended to choose the hospital-based CR program among all cases registered in the database. The top three diseases in the patients who participated in CR were CHD, hypertension, and metabolic syndrome (MS). Centers with CR were more likely to be tertiary-level hospitals. After adjusting for baseline values, there were significant differences in post-CR exercise capacity among the three groups (home-based CR group, hospital-based CR group, and hybrid CR group), which were in favor of the hybrid CR group compared with other groups. The underutilization of CR is a global issue, not just in China. Despite the number of CR programs showing an increasing trend in the past years, CR in China is still in the preliminary stage of development. Furthermore, the participation of CR in China shows wide diversity across geography, disease, age, sex, risk stratification, and hospital-level factors. These findings reinforce the importance of the implementation of effective measures to improve the participation, enrollment in, and uptake of cardiac rehabilitation.